SS18-rearranged false negative FISH synovial sarcoma: A rare case of primary renal synovial sarcoma with cryptic genetic rearrangement - Teo, Kai Zong; Wright, Dale; Kim, Lawrence; Dinh, Phuong; Kim, Lauren (Current problems in cancer. Case reports, 2025)
Primary renal synovial sarcoma is an extremely rare malignancy with fewer than 200 cases reported in the literature. We present a case of a 34-year-old female who presented to hospital with right flank pain and was found to have a 12 cm renal mass on imaging complicated by haemorrhage and requiring emergency nephrectomy. Histopathological examination revealed a monophasic spindle cell tumour with large areas of necrosis, high-grade morphology and positive staining of SS18-SSX and TLE1 immunohistochemistry, consistent with a poorly differentiated synovial sarcoma. Fluorescence in-situ hybridisation (FISH) testing for SS18 showed no rearrangement. However, RNA sequencing identified a SS18::SSX2 gene fusion transcript that likely reflects a cryptic structural gene rearrangement. This case highlights the importance of molecular testing in diagnosing synovial sarcoma, particularly in cases with atypical presentations or false-negative FISH results.